2012
DOI: 10.3389/fonc.2012.00094
|View full text |Cite
|
Sign up to set email alerts
|

Mouse genetic approaches applied to the normal tissue radiation response

Abstract: The varying responses of inbred mouse models to radiation exposure present a unique opportunity to dissect the genetic basis of radiation sensitivity and tissue injury. Such studies are complementary to human association studies as they permit both the analysis of clinical features of disease, and of specific variants associated with its presentation, in a controlled environment. Herein I review how animal models are studied to identify specific genetic variants influencing predisposition to radiation-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
(74 reference statements)
2
18
0
Order By: Relevance
“…Variations in the response to radiation exposure between inbred mouse strains has been well established. Differences in susceptibility to DNA damage and cell death, as well as differences in tissue responses and repair mechanisms, have been previously reported as the underlying mechanisms [5052]. For example, greater radiation-induced DNA damage occurs in BALB/c mice, a radiation-sensitive strain, when compared to DNA damage in C57BL/6J mice, a radiation resistant strain in this context [53].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the response to radiation exposure between inbred mouse strains has been well established. Differences in susceptibility to DNA damage and cell death, as well as differences in tissue responses and repair mechanisms, have been previously reported as the underlying mechanisms [5052]. For example, greater radiation-induced DNA damage occurs in BALB/c mice, a radiation-sensitive strain, when compared to DNA damage in C57BL/6J mice, a radiation resistant strain in this context [53].…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been employed extensively in associating distinct radiobiological phenotypes with certain candidate genes aimed at allowing the recognition of sensitive patients undergoing radiation therapy and identifying targets for therapeutic intervention (26–28). However, some mouse models produce a response that are not reflected in the human phenotype and may therefore render the applicability of genetic analyses invalid.…”
Section: Discussionmentioning
confidence: 99%
“…These animals were chosen because previous reports had demonstrated that this model presented with locally advanced disease (19) instead of widespread metastases, which common in models that use the Trp53 R172H mutant knock-in construct (20). Moreover, our KPC animals were backcrossed to C57BL/6 genetic background over 10 generations to reduce potential variability in normal tissue radiation responses that often occurs in mixed backgrounds (21). The experimental schema is shown in Fig 3A. KPC mice with the appropriate genotype were screened for tumors by weekly ultrasounds beginning at 16 weeks of age.…”
Section: Radiation Therapy With Egln Inhibition Improves Survival In mentioning
confidence: 99%
“…The administration of high-dose radiation therapy of >65Gy (high-dose) with or without radioprotection improved survival compared to all animals that received ≤65Gy (low-dose) of treatment or no RT ( Fig 3B; 37 days [95% CI [33][34][35][36][37][38][39][40][41] vs. 15 days [10][11][12][13][14][15][16][17][18][19][20][21] vs. 15 days [10-20], respectively; p=0.005). The median overall survival was compared amongst the treatment groups and was highest ( Fig 3C;…”
Section: Radiation Therapy With Egln Inhibition Improves Survival In mentioning
confidence: 99%